Fostering CHANGE: Lessons from implementing a multi-country, multi-sector nutrition-sensitive agriculture project - Nordhagen, S.; Nielsen, J.; Mourik, Tom A. van; Smith, E.; Klemm, R. (Elsevier, 2019)
Using agriculture to improve nutrition is an approach growing in popularity, with programs becoming increasingly complex and multisectoral. While there is an active line of research assessing the impacts of such programs, little has been written about the process of successfully implementing them. As such, this paper uses a multisectoral nutrition-sensitive agriculture program implemented in four African countries as a case study to address key challenges in and lessons learned from implementation. We highlight the overall flexibility of nutrition-sensitive agriculture but also the need to adapt certain aspects to the particular context, as well as the opportunities for cross-context learning (and the limits to this). Integrating rigorous evaluation into such complex programs and forging diverse cross-sectoral partnerships offer both rewards and challenges, upon which we reflect. Main lessons learned from the program include the importance of carefully sequencing interventions, retaining flexibility in implementation, allowing for considerable time for cross-sector integration and coordination, and considering community impacts when designing research.